Identification of tyrosine 706 in the kinase insert as the major colony-stimulating factor 1 (CSF-1)-stimulated autophosphorylation site in the CSF-1 receptor in a murine macrophage cell line. - van der Geer, P (1990)
The receptor for colony-stimulating factor 1 (CSF-1) is a ligand-activated protein-tyrosine kinase. It has been shown previously that the CSF-1 receptor is phosphorylated on serine in vivo and that phosphorylation on tyrosine can be induced by stimulation with CSF-1. We studied the phosphorylation of the CSF-1 receptor by using the BAC1.2F5 murine macrophage cell line, which naturally expresses CSF-1 receptors. Two-dimensional tryptic phosphopeptide mapping showed that the CSF-1 receptor is phosphorylated on several different serine residues in vivo. Stimulation with CSF-1 at 37 degrees C resulted in rapid phosphorylation on tyrosine at one major site and one or two minor sites. We identified the major site as Tyr-706. The identity of Tyr-706 was confirmed by mutagenesis. This residue is located within the kinase insert domain. There was no evidence that Tyr-973 (equivalent to Tyr-969 in the human CSF-1 receptor) was phosphorylated following CSF-1 stimulation. When cells were stimulated with CSF-1 at 4 degrees C, additional phosphotyrosine-containing phosphopeptides were detected and the level of phosphorylation of the individual phosphotyrosine-containing phosphopeptides was substantially increased. In addition, we show that CSF-1 receptors are capable of autophosphorylation at six to eight major sites in vitro.